Antilisterial efficacy of Lactobacillus bacteriocins and organic acids on frankfurters. Impact on sensory characteristics - Castellano, Patricia Haydee (2018)
Dipping solutions containing bacteriocins produced by Lactobacillus curvatus CRL705 and Lactobacillus sakei CRL1862 (Bact705/1862), nisin and organic acids (lactic acid, LA; acetic acid, AA) were tested alone or in combination against Listeria monocytogenes inoculated by immersion on vacuum-packaged frankfurters stored at 10 °C during 36 days. LA/AA solution (2.5% v/v each) reduced pathogen population by 1.50 log10 CFU/ml during storage. Semi-purified Bact705/1862 prevented L. monocytogenes growth, while nisin was not able to avoid its regrowth after 20 days. The combined addition of Bact705/1862 + LA/AA was the most effective approach for pathogen reduction below detection level from day 6 to final storage. Frankfurters treated with Bact705/1862 + LA/AA compared to fresh-purchased samples did not show significant differences in flavor, juiciness, color intensity and overall preference at 22 days-storage at 5 °C. Meat processors should not only validate the antimicrobial efficacy of combined treatments but also their sensory impact on the product, which is directly related to consumer acceptability.